2020
DOI: 10.1002/jcb.29627
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circABCC4 regulates lung adenocarcinoma progression via miR‐3186‐3p/TNRC6B axis

Abstract: Lung adenocarcinoma (LUAD), a general kind of bronchogenic malignancy globally, is depicted as one of the most critical factors affecting human health severely. Featured with loop structure, circular RNA (circRNA) has been described as an essential regulator of multiple human malignancies. Nevertheless, knowledge concerning the regulatory function of circRNA in LUAD progression remains limited. Identified as a novel circRNA, circABCC4 has not been studied in LUAD as yet. This is the first time to probe into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…For example, circ_0013958 expression was positively correlated with lymphatic metastasis of LUAD patients [ 26 ]; a negative association between circCRIM1 and lymphatic metastasis and TNM stage of LUAD was verified [ 27 ]. Additionally, increasing evidence has demonstrated the functional roles of circRNAs in the progression of LUAD [ 13 , 14 , 28 ]. circXPO1 was responsible for LUAD progression and might be a therapeutic target for this disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, circ_0013958 expression was positively correlated with lymphatic metastasis of LUAD patients [ 26 ]; a negative association between circCRIM1 and lymphatic metastasis and TNM stage of LUAD was verified [ 27 ]. Additionally, increasing evidence has demonstrated the functional roles of circRNAs in the progression of LUAD [ 13 , 14 , 28 ]. circXPO1 was responsible for LUAD progression and might be a therapeutic target for this disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sponging miRNAs, which results in inhibition of target miRNA expression and subsequent enhancing levels of miRNA-targeted genes has been considered to be the main regulatory mechanism of circRNAs[ 12 ]. Increasing studies have revealed that circRNAs play crucial roles in affecting the malignant phenotypes of LUAD, including growth and metastasis[ 13 , 14 ]. A recent research by Feng et al suggested that hsa-circ-0000211 drove the migration and invasion of LUAD cells via enhancing HIF1-α expression by sequestering miR-622[ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The circRNAs, circABCC4 and circ0006916, were shown to interact with TNRC6 to positively and negatively regulate lung cancer progression, respectively. CircABCC4 was upregulated in LUAD and promoted cell proliferation, migration and invasion via miR-3186-3p sponging to upregulate TNRC6B ( 72 ). However, Circ0006910 was downregulated in lung cancer cells and tissue, and acted as a tumor suppressor in NSCLC via miR-522-3p sponging, and inhibiting pleckstrin homology domain and leucine rich repeat protein phosphatase 1 (PHLPP1) activity, thus inhibiting cell proliferation ( 73 ).…”
Section: The Role Of Circrnas In Lung Cancermentioning
confidence: 99%
“…Growing evidence suggests that circRNA can act as a miRNA sponge to mediate the expression of target mRNA [12]. Recently, it has been identified that several circRNAs participate in LUAD progression, such as circ-000032 [13], circ-PVT1 [14] and circ-ABCC4 [15]. Nevertheless, the function of most circRNAs in LUAD remains unknown.…”
Section: Introductionmentioning
confidence: 99%